2022
DOI: 10.3389/fnut.2022.885704
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Is the Key Cause of Overweight/Obesity in Sugar-Sweetened Beverages (SSB)

Abstract: To evaluate association between overweight/obesity and sugar-sweetened beverages (SSB) types, SSB sugar, among children and adolescents. A total of 1,068 children and 751 adolescents were identified from a provincial survey conducted in Shandong, China. χ2 tests, logistic regression, restricted cubic spline (RCS), mediation analysis, pathway analysis, and ordinary least square (OLS) regression were applied to test association among overweight/obesity, SSB sugar, SSB types, and a set of factors. The mean daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Our study found that the reduced consumption of SSBs is associated with lower BMI z-score gain in Chinese schoolchildren aged 9–10 years. To our best knowledge, this is the first trial to examine the effects of reducing the consumption of SSBs on BMI z-score gain among Chinese schoolchildren [ 3 , 15 , 17 , 30 , 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study found that the reduced consumption of SSBs is associated with lower BMI z-score gain in Chinese schoolchildren aged 9–10 years. To our best knowledge, this is the first trial to examine the effects of reducing the consumption of SSBs on BMI z-score gain among Chinese schoolchildren [ 3 , 15 , 17 , 30 , 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with recent reviews reporting that reducing the consumption of SSBs reduced weight gain and obesity in schoolchildren [ 18 , 24 , 25 ]. The excess intake of free sugars (all sugars added to foods) is a key contributor to unhealthy weight gain [ 17 ]. Ruyter et al indicated that the reduced ingestion of liquid sugars might also reduce the insulin spike and thus diminish hunger [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Public health measures have failed to provide such support, since obesity rates are rising rapidly with far-reaching health consequences (Kelly et al, 2008 ; Dixon, 2010 ). Although sugar is a key cause of obesity (Yu et al, 2022 ), there is limited research exploring what can influence individuals to consume less sugar. We have recently demonstrated that a healthy eating call by an expert can significantly decrease the willingness to pay (WTP) for sugar-containing food (Ntoumanis et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%